Draft Annual Plan For 1976-77 (Sectoral Plans) Government of Nagaland - Planning Commission (Planning Commission, 1975)
Nagaland is one of the tiny States of the North Eastern Hill Region bounded by the Arunachal Pradesh, Assam, Manipur and Burma on the -North, West, South and East respectively. It has a total geographical area of 16,488 Sq. Kms. and a population of 5.15 lakhs living in 966 villages according to the 1971 Census. Almost the entire population being tribal there is extensive prevalence of shifting cultivation. About 1,08,000 Ha. of land (6.6% of the total area) is cultivated in a year, of which 29,000 Ha. (1.8% of the total area) is under terrace cultivation. More than 75% of the cultivated area is still under jhuming. Therefore, agricultural development in the State faces certain inherent problems.
Planning and Co-ordination Department Government of Nagaland